Nasal microbiota and symptom persistence in acute respiratory tract infections in infants. Issue 4 (3rd December 2018) - Neumann, Roland P.; Hilty, Markus; Xu, Binbin; Usemann, Jakob; Korten, Insa; Mika, Moana; Müller, Loretta; Latzin, Philipp; Frey, Urs
Acute respiratory tract infections (ARI) in infancy have been implicated in the development of chronic respiratory disease, but the complex interplay between viruses, bacteria and host is not completely understood. We aimed to prospectively determine whether nasal microbiota changes occur between the onset of the first symptomatic ARI in the first year of life and 3 weeks later, and to explore possible associations with the duration of respiratory symptoms, as well as with host, environmental and viral factors. Nasal microbiota of 167 infants were determined at both time-points by 16S ribosomal RNA-encoding gene PCR amplification and subsequent pyrosequencing. Infants were clustered based on their nasal microbiota using hierarchical clustering methods at both time-points. We identified five dominant infant clusters with distinct microbiota at the onset of ARI but only three clusters after 3 weeks. In these three clusters, symptom persistence was overrepresented in the Streptococcaceae-dominated cluster and underrepresented in the cluster dominated by "Others" (p<0.001). Duration of symptoms was not associated with the type of respiratory virus. Infants with prolonged respiratory symptoms after their first ARI tend to exhibit distinct microbial compositions, indicating close microbiota–host interactions that seem to be of importance for symptom persistence and recovery. Nasal microbiota in infants is associated with symptom persistence after acute symptomatic respiratory infections. http://ow.ly/3Mhh30mC1wJ